Neoadjuvant Chemotherapy in Locally Advanced Gastric Cancer: What to Avoid. Preliminary Analysis of a Consecutive Series of Patients. Issue 5 (September 2015) - Rausei, Stefano; Lianos, Georgios D.; Proserpio, Ilaria; Ruspi, Laura; Galli, Federica; Frattini, Francesco; Mangano, Alberto; Rovera, Francesca; Boni, Luigi; Roukos, Dimitrios H.; Pinotti, Graziella; Dionigi, Gianlorenzo
Aims and background: The role of neoadjuvant (NAD) chemotherapy (CHT) in patients with locally advanced gastric cancer (LAGC) is validated. However, some important limitations emerged from the literature, including patient selection, quality of surgery, and pathologic response evaluation. Neoadjuvant CHT for LAGC has been evaluated with a focus on safety and efficacy of the preoperative approach in terms of patient compliance, surgical outcomes, and pathologic response. Methods and Study Design: Ninety-one patients with gastric adenocarcinoma were prospectively observed. All patients received computed tomography scan and laparoscopy staging. Ten patients with LAGC (including 2 with LAGC suspected for cM+/lapM+) had been recruited in the preoperative ECF/EOX CHT protocol and were compared with 61 patients who underwent surgery alone. Results: The overall compliance for the preoperative CHT group was higher than compliance for adjuvant CHT observed in both the NAD CHT group and the surgery alone group. There were 2 treatment shifts to FOLFOX in the preoperative regimen. In the preoperative CHT group, D2-gastrectomy was possible only in 6/10 of cases, with a R0 resection rate of 67% (versus 64% in the LAGC patients treated by surgery alone). The postoperative mortality and morbidity were 0% and 17% in the NAD CHT group versus 2% and 26% in the surgery alone group. The overall pathologic response rate after NAD CHT was 83% (5/6). Conclusions: Staging and CHT management problems can negatively affect patient outcomes. In the LAGC setting, when well applied, NAD CHT could be considered a valuable treatment option.